THE ROLE OF LEGAL EDUCATION AND THE MEDIA IN BOOSTING YOUTH MORALE (Scientific journal of the Fergana State University, 2023)
This article scientifically analyzes that legal education is the main factor and guarantee of building and strengthening a democratic state and civil society. In particular, it is said that the higher the legal knowledge, culture and spirituality of the population, the stronger the rule of law will be. In addition, issues such as the negative consequences of moral threats and the role of the media in preventing them when information and communication technologies penetrate into various spheres of society are highlighted.